2020
DOI: 10.1177/2150132720963634
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Artificial Intelligence and Machine Learning to Combat COVID-19 and Existing Opportunities for LMIC: A Scoping Review

Abstract: Background: In the face of the current time-sensitive COVID-19 pandemic, the limited capacity of healthcare systems resulted in an emerging need to develop newer methods to control the spread of the pandemic. Artificial Intelligence (AI), and Machine Learning (ML) have a vast potential to exponentially optimize health care research. The use of AI-driven tools in LMIC can help in eradicating health inequalities and decrease the burden on health systems. Methods: The literature search for this Scoping review was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 28 publications
1
52
0
1
Order By: Relevance
“…In this regard, multiple research projects have been published using machine/deep learning techniques for the early detection of the COVID-19 virus [ 22 , 23 , 24 , 25 ], models applied to patients admitted to ICUs, which have been the clinical units most affected by the virus [ 26 , 27 , 28 ], and machine/deep learning applied in “omic” technologies to predict complications of COVID-19 [ 29 , 30 ]. The number of published papers about COVID-19 is continuously growing [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, multiple research projects have been published using machine/deep learning techniques for the early detection of the COVID-19 virus [ 22 , 23 , 24 , 25 ], models applied to patients admitted to ICUs, which have been the clinical units most affected by the virus [ 26 , 27 , 28 ], and machine/deep learning applied in “omic” technologies to predict complications of COVID-19 [ 29 , 30 ]. The number of published papers about COVID-19 is continuously growing [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…AI, and more specifically machine learning models, are increasingly used in disease surveillance and can maximise the impact of limited available resources. 14 Integration of such models with accurate digital epidemiological data was shown to provide reliable, near real-time estimations of influenza disease incidence. 15 The widespread distribution of smartphones coupled with the development of AI-enabled sound classification models now represent another new potential breakthrough in public health and epidemic preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…The latter also discusses how other technologies such as AI, IoT, and unmanned aerial vehicles (UAVs) can facilitate better management of the pandemic through improving, among other things, diagnosis, surveillance, and treatment capacities [2]. Focusing on the applications in the health sector, Naseem et al [13] also found that AI-enabled solutions are effective in timely and accurate identification and monitoring and tracing of COVID-19 cases. While these reviews have been successful in highlighting the utilities of smart solutions, they are mainly sector-based (i.e., the health sector).…”
Section: Introductionmentioning
confidence: 99%